Triacylglycerols Based on 2-(N-tert-Butoxycarbonylamino)oleic Acid Are Potent Inhibitors of Pancreatic Lipase - Magrioti, V.; Verger, R.; Constantinou-Kokotou, V. (Journal of Medicinal Chemistry, 2004)
A novel class of potent human pancreatic lipase (HPL) inhibitors was developed. Triacylglycerol analogues containing 2-(N-tert-butoxycarbonylamino) fatty acids were synthesized, and their ability to form stable films at the air/water interface was studied. The inhibition of human digestive lipases by the compounds synthesized was studied by the monolayer technique, and the triesters of glycerol and 2-methylglycerol with 2-(N-tert-butoxycarbonylamino)oleic acid were found to be potent inhibitors of HPL.